Determination of HeaDetermination of Some Heavy Metals in Three Fish Species from Duhok City Markets in Kurdistan of Iraq - Ahmed, Shahyan S.; Hasan, Mahmood A. (Science Journal of University of Zakho, 2019)
In this study, the concentrations of some heavy metals including Al, Cu, Fe, Mn, Zn, Cd, Co, Cr, Ni and Pb were determined in the muscles of three commercial fish species available in Duhok city markets in two seasons, using inductively coupled plasma-optical emission spectrometry (ICP-OES), after the wet digestion process. Lowest and highest mean values of metals in µg/g (dry weight) were as follows: Al: Under Detection Limit (UDL)-3.71, Cu: UDL-4.00, Fe: 5.40-21.44, Mn: UDL-3.45, Zn: 13.38-140.11, while Cd, Co, Cr, Ni, and Pb were not detected. The highest levels of Al, Fe and Zn were recorded in Shukhat fish species, and the highest levels of Cu and Mn were recorded in Shabout in the winter season. The highest level of all metals was recorded for Zn (172.8 µg/g) with the highest mean value of (140.11 µg/g) in Shukhat species during winter. Most heavy metal concentrations were below the international permissible limits for fish, however, some of the maximum and mean values of metals were above the international standards. Fe concentrations were above the maximum allowable limits set by WHO (1999). Zn concentrations were above the maximum permissible limits set by joint FAO/WHO (1989) and FAO (2012).